The Role of the Neuronal gap Junction Protein Connexin36 in Kainic Acid Induced Hippocampal Excitotoxicity - Akins, Mark S. (Université d'Ottawa / University of Ottawa, 2014)
Kainic acid induced excitotoxicity causes pyramidal cell death in the CA3a/b region of the hippocampus. Electrical synapses, gap junctional communication, and single membrane channels in non-junctional membranes (hemichannels) composed of connexin36 (Cx36) have been implicated in both seizure propagation and the spread of excitotoxic cell death. In rats, Cx36 protein is expressed by pyramidal neurons. Localization of protein in mouse, however, is highly controversial. Expression is reported to be restricted to hippocampal interneurons yet the same excitotoxic mechanisms (electrical and metabolic coupling between pyramidal neurons) are invoked to explain the role of Cx36 in excitotoxic pyramidal loss in murine brain. To address this controversy, I show by confocal immunofluorescence and in situ hybridization that Cx36 protein expression is restricted to interneurons and microglia in murine hippocampus and is not expressed by, or is below level of detection in pyramidal neurons. Using behavioural and electrophysiological measures, seizure propagation was found to be moderately enhanced in the absence of Cx36 likely due to the loss of interneuron-mediated synchronous inhibition of the pyramidal cells. Further, CA3a/b neurons die post kainic acid injury in the presence of Cx36 but are protected in Cx36-/- mice. When delayed excitotoxic cell death is maximal, Cx36 is primarily expressed by activated microglia as demonstrated by confocal immunofluorescence, in situ hybridization, and Western blotting. These activated microglia are located in the direct vicinity of, and surrounding cells in the damaged Ca3a/b region. Finally, I show that loss of Cx36 from activated microglia in mice is sufficient to prevent excitotoxic cell death in the CA3a/b with surviving neurons functional as assessed by both electrophysiological and behavioural measures. Together, these data identify a new mechanism of excitotoxic injury, mediated by neuronal-glial interactions, and dependent on microglial Cx36 expression.
Keywords: Kainic acid; Excitotoxic injury; Excitotoxicity; Neuron; Neuronal survival; Connexin36; Connexin; Pyramidal cell; Interneuron; Hippocampus; Microglia; Neural protection; Seizure